The Phishing Game: An Analog Game To Defend UK Organisations From Phishing - Henderson, Niklas (Cranfield University, 2024)
Poster contribution to the Defence and Security Doctoral Symposium 2023
Keywords: Phishing; serious game; disinformation; inoculation; security; cyber; cybersecurity; DSDS23; DSDS23 Poster